Pengaruh Kepemimpinan, Iklim Organisasi, dan Motivasi Kerja Terhadap Disiplin Kerja Pegawai Negeri Sipil Pada Dinas Pendidikan Pemuda Dan Olahraga Kota Bukittinggi - Miaz, Okki Trinanda (Jurnal Ekonomi, 2012)
Decreasing in dicipline shows by employee or civil official becoming an important issue. This research purposed to identify employee diciplinie influenced by leadership, organization climate, and motivation in Dinas Pendidikan Pemuda dan Olahraga Bukittinggi. Proportional stratified random sampling used to identify research sampling 81 person of civil officials. Hypotesis determined by structural equation model with AMOS package. The research result shows leadership have not significant influenced to create organization climate supporting. But, leadership have a significant correlated to motivation and employee dicipline, although organizational climate have not significant correlated to employee dicipline. According to this result, to increase employee dicipline in Dinas Pendidikan Pemuda dan Olahraga Bukittinggi must have efforts for instances leader supposed to be a motivator to create organization climate with participated leadership and leadership must be key factor to build both of correlation to increase employee dicipline.